State Jurisdiction over Ice Island T-3 : The Escamilla Case - Pharand, Donat (ARCTIC, 1971)
The matter of State jurisdiction over ice islands in the Arctic Ocean is no longer only an academic question raised by professors of international law. A recent incident involving the killing of a member of an American research team on Ice Island T-3 raises that question in a very realistic way. The purpose of this short paper is to review the relevant facts and to offer a few comments on the issue of jurisdiction in the light of the legal nature of the Arctic Ocean and of Ice Island T-3. On 16 July 1970, the shooting of the leader of a 20-man joint government-industry research team, one Bennie Lightsy of Louisville, Kentucky, took place in a hut on Ice Island T-3 (the third ice island sighted as a radar target, hence its name T-3), floating in the Arctic Ocean at 84° 47' North latitude and 106° 28' West longitude, within the so-called Canadian sector. Lightsy had gone to the hut to attempt to settle an argument over a jug of wine when he was shot with a rifle by one Mario Escamilla, a Mexican-born American citizen from California. Following a radio report about the incident, an American investigation team, composed of Naval and Coast Guard Intelligence officers and an Assistant U.S. Attorney, flew to Thule, an American Air Force Base in Greenland, and then to the ice island in question. Upon completion of the investigation, Escamilla was brought to the United States, after a change of plane at Thule, and landed at Dulles airport in Virginia. He was initially charged with murder in the first degree before a magistrate in the District Court for the Eastern District of Virginia, within which Dulles airport is located, and was subsequently indicted by a grand jury for the lesser offence of second degree murder. The issue raised is whether the United States or Canada, or both, had jurisdiction over the alleged crime committed on Ice Island T-3. The complaint stated that the ice island was floating on the high seas within the special maritime and territorial jurisdiction of the United States of America and out of the ...